Is There Less Alteration of Smell Sensation in Patients With Omicron SARS-CoV-2 Variant Infection? - Rodriguez-Sevilla, Juan Jose; Güerri-Fernádez, Roberto; Bertran Recasens, Bernat (Frontiers in Medicine, 2022)
The ongoing pandemic Coronavirus Disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a matter of global concern in terms of public health Within the symptoms secondary to SARS-CoV-2 infection, hyposmia and anosmia have emerged as characteristic symptoms during the onset of the pandemic. Although many researchers have investigated the etiopathogenesis of this phenomenon, the main cause is not clear. The appearance of the new variant of concern Omicron has meant a breakthrough in the chronology of this pandemic, presenting greater transmissibility and less severity, according to the first reports. We have been impressed by the decrease in anosmia reported with this new variant and in patients reinfected or who had received vaccination before becoming infected. Based on the literature published to date, this review proposes different hypotheses to explain this possible lesser affectation of smell. On the one hand, modifications in the SARS-CoV-2 spike protein could produce changes in cell tropism and interaction with proteins that promote virus uptake (ACE-2, TMPRSS2 and TMEM16F). These proteins can be found in the sustentacular cells and glandular cells of the olfactory epithelium. Second, due to the characteristics of the virus or previous immunity (infection or vaccination), there could be less systemic or local inflammation that would generate less cell damage in the olfactory epithelium and/or in the central nervous system.